2008
DOI: 10.1105/tpc.107.052670
|View full text |Cite
|
Sign up to set email alerts
|

An Inositol Polyphosphate 5-Phosphatase Functions in PHOTOTROPIN1 Signaling in Arabidopis by Altering Cytosolic Ca2+

Abstract: Inositol polyphosphate 5-phosphatase (5PTase) is a key enzyme in the phosphatidylinositol metabolic pathway, which plays critical roles in a number of cellular processes in plants. Our previous work implicated the role of 5PTase13, which encodes a WD40-containing type II 5PTase, in hormone-mediated cotyledon vein development. Here, we show that 5PTase13 is also involved in blue light responses in Arabidopsis thaliana. Compared with that in darkness, the expression of 5PTase13 was suppressed by blue light irrad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
52
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 52 publications
(53 citation statements)
references
References 85 publications
1
52
0
Order By: Relevance
“…The stereochemistry of D-myo-inositol suggested that the inositol ring represents a 6-bit signaling scaffold with the potential to "encode" 64 unique signaling states (York, 2006). In plants, InsP 3 has been associated with a wide range of cellular functions, such as guard cell physiology (Blatt et al, 1990;Gilroy et al, 1990;Burnette et al, 2003;Han et al, 2003), drought tolerance (Knight et al, 1997;Perera et al, 2008), heat shock responses (Liu et al, 2006), blue light perception (Chen et al, 2008), root gravitropism (Wang et al, 2009;Zhang et al, 2011), response to mechanical wounding (Mosblech et al, 2008), and pollen dormancy (Y. . However, the role of InsP 3 and other inositol phosphates in plant signaling remains controversial as no inositol phosphate receptor has been identified to date (Munnik and Vermeer, 2010;Munnik and Nielsen, 2011;Gillaspy, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…The stereochemistry of D-myo-inositol suggested that the inositol ring represents a 6-bit signaling scaffold with the potential to "encode" 64 unique signaling states (York, 2006). In plants, InsP 3 has been associated with a wide range of cellular functions, such as guard cell physiology (Blatt et al, 1990;Gilroy et al, 1990;Burnette et al, 2003;Han et al, 2003), drought tolerance (Knight et al, 1997;Perera et al, 2008), heat shock responses (Liu et al, 2006), blue light perception (Chen et al, 2008), root gravitropism (Wang et al, 2009;Zhang et al, 2011), response to mechanical wounding (Mosblech et al, 2008), and pollen dormancy (Y. . However, the role of InsP 3 and other inositol phosphates in plant signaling remains controversial as no inositol phosphate receptor has been identified to date (Munnik and Vermeer, 2010;Munnik and Nielsen, 2011;Gillaspy, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…For chloroplast movement responses the nucleus is not even required [20]. In contrast, gene expression changes are essential for phototropism [27,28] and presumably occur following the asymmetric distribution of auxin that is required for directional growth [28]. Such changes in gene expression are hard to record by whole plant analysis because they occur in specific cells [28,32].…”
Section: Phototropin Kinase Activity and Signal Transductionmentioning
confidence: 99%
“…Phot1 negatively regulates the expression of an inositol polyphosphate 5-phosphatase gene, which modulates inhibition of hypocotyl growth via Ca 2+ concentration regulation. Unfortunately, it is unknown whether this protein is also required for phototropism [27]. Growth responses such as phototropism require auxin and brassinosteroids [28][29][30][31] while there is no evidence suggesting that these hormones are involved in the control of chloroplast movements.…”
Section: Phototropin Kinase Activity and Signal Transductionmentioning
confidence: 99%
“…Arabidopsis ACTIN gene (At5g09810) was amplified with primers (5Ј-CCGGTATTGTGCTCGATTCTG-3Ј and 5Ј-TTCCCGTTCTGCGGTAGTGG-3Ј) and used as positive internal control. Primers of 5PT13 have been previously described (Chen et al, 2008). All the experiments were repeated three times.…”
Section: Quantitative Real-time Rt-pcr (Qrt-pcr) Analysismentioning
confidence: 99%
“…FRA3 is required for secondary wall synthesis and actin organization in fiber cells , and CVP2-mediated Ins(1,4,5)P 3 signal transduction is essential for closed venation patterns of Arabidopsis foliar organs (Carland and Nelson, 2004). In addition, 5PTs participate in seedling growth (Gunesekera et al, 2007;Ercetin et al, 2008) and blue-light signaling via the regulation of Ins(1,4,5)P 3 / [Ca 2+ ] cyt (Chen et al, 2008), and are important regulators of Ins(1,4,5)P 3 -mediated ABA signaling (Sanchez et al, 2001;Burnette et al, 2003;Lin et al, 2005;Gunesekera et al, 2007). However, no 5PTs have been reported to function in the regulation of reproductive development.…”
Section: Introductionmentioning
confidence: 99%